On the representation of groups approximated by finite p-groups - Leonov, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Faithful triangular representations of finite Kaloujnine p-groups are presented. This allows us to obtain a triangular representation of the projective limit P_p of groups P_p,n. The obtained representation is studied by using a language of matrix templates specially developed for this purpose. As an example, we present a triangular representation of the well-known self-similar Gupta – Sidki 3-group.